2022
DOI: 10.1002/14651858.cd000093.pub6
|View full text |Cite
|
Sign up to set email alerts
|

Cephalomedullary nails versus extramedullary implants for extracapsular hip fractures in older adults

Abstract: BackgroundHip fractures are a major healthcare problem, presenting a substantial challenge and burden to patients, healthcare systems and society. The increased proportion of older adults in the world population means that the absolute number of hip fractures is rising rapidly across the globe. Most hip fractures are treated surgically. This Cochrane Review evaluates evidence for implants used to treat extracapsular hip fractures. Cephalomedullary nails versus extramedullary implants for extracapsular hip frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 128 publications
3
48
0
1
Order By: Relevance
“…Authors of this interesting review from the UK found 76 eligible studies looking at either unstable trochanteric fractures, stable trochanteric fractures, subtrochanteric fractures, or a mixture of fracture types (the majority of studies) with the mean ages of studies ranging from 54 to 85 years. 3 The aim of the review was to establish the state of play with the evidence for one implant type over another. In comparing cephalomedullary nails with extramedullary implants, the authors found little or no difference in mortality within four months based on moderate-certainty evidence, and reported being unsure about findings related to performance of daily activities and mobility.…”
Section: Cephalomedullary Nails Versus Extramedullary Implants For Ex...mentioning
confidence: 99%
“…Authors of this interesting review from the UK found 76 eligible studies looking at either unstable trochanteric fractures, stable trochanteric fractures, subtrochanteric fractures, or a mixture of fracture types (the majority of studies) with the mean ages of studies ranging from 54 to 85 years. 3 The aim of the review was to establish the state of play with the evidence for one implant type over another. In comparing cephalomedullary nails with extramedullary implants, the authors found little or no difference in mortality within four months based on moderate-certainty evidence, and reported being unsure about findings related to performance of daily activities and mobility.…”
Section: Cephalomedullary Nails Versus Extramedullary Implants For Ex...mentioning
confidence: 99%
“…In the literature, both intramedullary (IM) Nails and Dynamic Hip Screws (DHS) have shown favourable results. 1 - 3 …”
Section: Introductionmentioning
confidence: 99%
“…In the literature, both intramedullary (IM) Nails and Dynamic Hip Screws (DHS) have shown favourable results. [1][2][3] The decision of whether to use IM Nail vs DHS is not consistently applied in practice. In principle, IM Nail is a stronger construct than the DHS fixation.…”
Section: Introductionmentioning
confidence: 99%
“…The most recent trials comparing SHS and nails, however, may indicate an improvement in nail design and technique. The increased risk of peri-implant fracture with nails persists, but is balanced by fewer complications in other areas, as indicated in the recently published Cochrane Review (1). Still, this does not explain the change in treatment that came before these results were available.…”
mentioning
confidence: 98%
“…Still, this does not explain the change in treatment that came before these results were available. With the current knowledge, it is not possible to give a strong recommendation on whether to use SHS or IMN, based on complications and functional results (1).…”
mentioning
confidence: 99%